Vyuzitelnost vaginální ultrasonografie jako prebioptické 7 6es.gynek. metody v diagnostice karcinomu delozního tela prostrednictvím stanovení tzv. EMI (endometrium/myometrium index) - Minái, L; Chovanec, J (Ceska gynekologie, 2006)
OBJECTIVE: The verification of the predicive part of the vaginal ultrasonography in diagnostics of cancer of endometrium with the help of comparison of vaginal sonography finding (through the mediation EMI--endometrium/myometrium index) with relevant histological results. DESIGN: Clinical prospective study. SETTING: Department of Gynaecology and Obstetrics, Faculty of Medicine, Masaryk University and Faculty Hospital, Brno. METHODS: In this work we included 200 patients--on one hand the patients with the symptoms (pre- and perimenopauzal irregular bleeding and postmenopauzal bleeding), on the other hand the patients without symptoms, but with the suspicious ultrasonography find (suspicious or positive EMI). Each of the patients included in this study underwent the ultrasonography examination witch determined EMI and then the endometrial biopsy or the diagnostic hysteroscopy with sampling the material. The determined value EMI was compared with the histological result. RESULTS: On the basis of the results of this work we found out the possibility utilization of the vaginal ultrasonography as the prebioptic method in diagnostics cancer of endometrium through the mediation of determined EMI. The sensitivity of the method, however, is lowered by the next diseases of uterus (especially uterine myoma) that cause wrong negativity of EMI with connection with increased thickness of uterus in the region body of uterus. CONCLUSION: We can expect a high sensitivity of EMI in patients with diseases of endometrium, if there is by ultrasonography examination verified uterus with smooth border without uterine myoma. This examination acquires a special significance as the pre-bioptic and along with the preventive method the timely catch first of all in patients without symptoms, but with one or more risk factors for rise to cancer of endometrium.
Keywords: nádory endometria; dospělí; Female; ultrasonografie; Adult; ženské pohlaví; endometrium; lidé; Uterine Neoplasms; Sensitivity and Specificity; Ultrasonography; Aged, 80 and over; senzitivita a specificita; nádory dělohy; Aged; Endometrium; lidé středního věku; Endometrial Neoplasms; senioři nad 80 let; senioři; myometrium; Middle Aged; Myometrium; Humans